Determinant of incentive Factors in Knowledge Sharing (Study at Multimedia University) - Saeed Behjati, (2009)
The main focus on this research is based on social factors considering (predecessor phase) and Knowledge absorption (successor phase) abreast of its focus in knowledge dissemination.